Multidisciplinary healthcare teams' challenges and strategies in supporting people with type 1 diabetes to recover from disordered eating. Issue 12 (23rd December 2019) - Zaremba, N.; Watson, A.; Kan, C.; Broadley, M.; Partridge, H.; Figuereido, C.; Hopkins, D.; Treasure, J.; Ismail, K.; Harrison, A.; Stadler, M.
Abstract: Aim: To examine the challenges healthcare teams face when treating people with type 1 diabetes and disordered eating and the strategies these teams have developed to facilitate effective treatment. Methods: Four semi‐structured focus groups were conducted including two tertiary diabetes specialist teams and three tertiary eating disorders specialist teams between July and December 2018. Thematic analysis of the transcripts followed a six‐phase process. Results: Twenty‐nine experienced healthcare professionals (16 diabetes and 13 eating disorder specialists, 16±12 years' professional experience) were interviewed. The challenges identified in treating people with type 1 diabetes and disordered eating included subthemes the 'challenges specific to the healthcare professional' (feeling not competent enough and perceived emotional burden), 'challenges pertaining to patient factors' (e.g. difficulties with engaging in therapy) and 'challenges created by the healthcare system' (time pressure and staff shortage). Healthcare professionals expressed the need for a consensus on diagnosis and the definition of disordered eating in type 1 diabetes, as well as the need for training and educational resources specific to type 1 diabetes and disordered eating. Healthcare professionals gave practical examples of strategies of communication for better patient engagement and felt that multidisciplinary working in joint clinics with the other specialty were facilitators for recovery from disordered eating. Conclusions: Healthcare professionals require multidisciplinary team support when treating people with type 1 diabetes and to improve their own competencies. The development of effective screening and assessment tools, educational resources and training for healthcare professionals, and developing multidisciplinary treatment pathways will be key to improving outcomes for their service users with type 1 diabetes and disordered eating. What's new?: People with type 1 diabetes and disordered eating experience high complication rates and are difficult to treat because there are no evidence‐based care pathways for this dual condition. This study offers insights into the challenges of treating people with type 1 diabetes and disordered eating and the self‐acquired strategies used by healthcare teams in tertiary diabetes and eating disorder centres to overcome these challenges. We identified the gaps in professional consensus, training and guidance for healthcare professionals. The findings will be used to develop the STEADY intervention (the Safe Management of People with Type 1 diabetes and Eating Disorders Study)